The influence of organizational and individual factors on Nurses’ compliance with re-assessment of patient fall risk - Wagiyo Wagiyo; Ossy Wijaya Iriandoko; Djazuly Chalidyanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The report on the average achievement of nurses’ compliance with the reassessment of patients’ fall risk from January to June 2020 was 54.75% and did not meet the average hospital standard of 100%. This study aims to analyze the influence of organizational and individual factors on nurses’ compliance with the re-assessment of fall risk at the inpatient installation of RSPAL dr. Ramelan Surabaya. This was an analytical observational study with a cross- sectional design. 162 people were taken as the respondents using a proportionate simple random sampling technique. The results of strategic issues and Focus Group Discussion (FGD) showed that nurse peer support in the fairly supportive category (75.9%). The result of measuring the nurses’ compliance with performing the re-assessment of fall risk is in the High category (89.5%). The factors, including supervision, information, the proximity of authority, the location status, personal responsibility, the legitimacy of authority figure, the status of authority figure, and peer support, significantly affect the nurses’ compliance with performing the reassessment of patients’ fall risk. The increase in the nurses’ compliance level in performing the re-assessment of fall risk correctly can be achieved by conducting an outreach to all nurses regarding the effects of performing the re-assessment of fall risk incorrectly, and conducting a regular outreach to heads of nursing room to actively evaluate and motor the implementation of the re-assessment of fall risk. Abstrak: Laporan pencapaian rata-rata kepatuhan perawat terhadap asesmen ulang pasien risiko jatuh periode Januari sampai Juni 2020 sebesar 54,75% dan tidak memenuhi standar rata-rata rumah sakit sebesar 100%. Penelitian ini bertujuan untuk menganalisis pengaruh faktor organisasi dan faktor individu terhadap kepatuhan perawat pada penilaian ulang risiko jatuh di instalasi rawat inap RSPAL dr. Ramlan Surabaya. Penelitian ini merupakan penelitian observasional analitik dengan desain cross-sectional. Sebanyak 162 orang diambil sebagai responden dengan menggunakan teknik proportional simple random sampling. Hasil strategic issues dan Focus Group Discussion (FGD) menunjukkan bahwa peer support perawat dalam kategori cukup mendukung (75,9%). Hasil pengukuran kepatuhan perawat dalam melakukan asesmen ulang risiko jatuh berada pada kategori Tinggi (89,5%). Faktor-faktor yang meliputi supervisi, informasi, kedekatan otoritas, status lokasi, tanggung jawab pribadi, legitimasi figur otoritas, status figur otoritas, dan dukungan sebaya berpengaruh signifikan terhadap kepatuhan perawat dalam melakukan asesmen ulang pasien jatuh. mempertaruhkan. Peningkatan tingkat kepatuhan perawat dalam melakukan asesmen ulang risiko jatuh dengan benar dapat dicapai dengan melakukan sosialisasi kepada seluruh perawat mengenai dampak dari salah melakukan asesmen ulang risiko jatuh, dan melakukan sosialisasi secara berkala kepada kepala ruangan. ruang perawatan untuk secara aktif mengevaluasi dan menggerakkan pelaksanaan asesmen ulang risiko jatuh.